2016
DOI: 10.1111/eje.12183
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of the first cohort of student groups trained together at the University of Portsmouth Dental Academy towards dental interprofessional education

Abstract: The findings suggest that IPE was perceived as beneficial in relation to teamwork; however, the study raises issues regarding professional identity and roles. Educators should consider differing perceptions of professional roles and identities when planning and delivering interprofessional programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
2
20
1
1
Order By: Relevance
“…Methodological differences existed in teaching, curricula, and placements between undergraduate- and postgraduate-level IPE programs. Seventeen studies reported postgraduate level IPE programs on children palliative care, [ 38 ] dental care, [ 32 , 45 , 47 ] social work, [ 26 , 54 ] and gerontology. [ 36 , 64 ] Undergraduate-level IPE programs emphasized the interdisciplinary collaboration, professionals in health care and team work, [ 18 ] dental care, [ 33 , 36 ] crisis management, [ 70 ] palliative oncology care, [ 19 ] ethics and professionalism training, [ 60 ] and psychosocial oncology practice and research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Methodological differences existed in teaching, curricula, and placements between undergraduate- and postgraduate-level IPE programs. Seventeen studies reported postgraduate level IPE programs on children palliative care, [ 38 ] dental care, [ 32 , 45 , 47 ] social work, [ 26 , 54 ] and gerontology. [ 36 , 64 ] Undergraduate-level IPE programs emphasized the interdisciplinary collaboration, professionals in health care and team work, [ 18 ] dental care, [ 33 , 36 ] crisis management, [ 70 ] palliative oncology care, [ 19 ] ethics and professionalism training, [ 60 ] and psychosocial oncology practice and research.…”
Section: Resultsmentioning
confidence: 99%
“…IP clinical placements were typically based in hospitals, communities, or a combination of the 2 places. The profession-specific clinical practice was reported in 1 study [ 32 ] and an unstructured IP clinical practice in the curricula was identified across the IPE programs. A few studies showed that evidence-based clinical practice took place in the department of social work IPE initiatives.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study from Saudi Arabia showed that DHs had a low level of knowledge about the oral-systemic diseases relationship. [29] Several studies highlighted many benefits of inter-professional collaboration both within oral health teams as well as with general health care[21430] The present study showed that one third of the DH in Sweden and Portugal sometimes worked with other oral health professionals.…”
Section: Discussionmentioning
confidence: 58%
“…It was further suggested that the attitudes of academic staff reinforced these divisions that were not so evident in the early years of studies . Another IPE study with students from dentistry, dental hygiene and therapy and dental nursing in the UK has shown that although IPE was perceived as beneficial in relation to teamwork and collaboration, dentists had a higher preference for an exclusive professional identity to learning compared to other disciplines …”
Section: Discussionmentioning
confidence: 99%